Barriers to effective outpatient hypertension treatment: a view of physicians and patients - S. V. Nedogoda; A. V. Sabanov; O. I. Bychkova (Российский кардиологический журнал, 2020)
Aim. To study the opinion of primary care physicians and hypertensive (HTN) outpatients with different compliance rate on factors preventing effective antihypertensive therapy (AHT).Material and methods. Primary care physicians and HTN outpatients were questioned. Questionnaires for physicians and patients included informative and survey parts, with a list of possible factors aggravated adherence to treatment. The assessment was carried out using visual analogue scale. The patient questionnaire also included questions about AHT and the eight-item Morisky Medication Adherence Scale (MMAS-8). The calculation was carried out with a 95% confidence interval (CI).Results. The survey involved 298 physicians and 517 patients. Among patients, about 1% had a high compliance rate, 34% — moderate, 65% — low. In all groups, AHT did not significantly differ and was characterized by a low frequency of prescribing fixeddose combinations (27,1%). According to physicians, the most significant and equivalent are the economic aspects of treatment — 7,9±2,1 (95% CI: 7,51-8,38), the need for lifestyle change — 7,9±2,4 (95% CI: 7,37-8,38) and, to a slightly lesser extent, psychological aspects 6,8±2,2 (95% CI: 5,43-6,43). The economic aspects of treatment and need for lifestyle change were also most significant factors according to patients with high (8,8±1,8 (95% CI: 7,23-10,37) and 8,4±1,7 (95% CI: 6,93-9,87), respectively) and low (95% CI: 6,4±3,0 (5,65-7,07) and 6,2±2,8 (95% CI: 5,5-6,82) respectively) compliance rates. For patients with moderate compliance rate, the most significant and almost equivalent factors were the need for lifestyle change — 5,6±3,3 (95% CI: 4,53- 6,71), the need for regular visits — 5,6±3,1 (95% CI: 4,53-6,58) and the need for selfmanagement — 5,6±2,8 (95% CI: 4,63-6,48).Conclusion. The results obtained make it possible to forecast the compliance rate of patients with HTN, and, therefore, direct more efforts to those with a low rate, thereby increasing the effectiveness of AHT.